Learning Model Optimization Project Based Learning (PjBL) Engineering Physics Course as an Effort to Increase Student Creativity - Hanifati, Sarah Najla (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The purpose of this study is to optimize the Project Based Learning (PjBL) learning model as an effort to improve the creativity of Electrical Engineering Education students at the State University of Jakarta in learning the Engineering Physics I subject. The Engineering Physics I subject is an important subject role in the initial conceptual understanding of Electrical Engineering students, especially in other Electrical Engineering subjects. Engineering Physics learning is very important as an initial foundation for students in the future. There are still students who do not understand the Engineering Physics material so that there needs to be a change in the learning model that can improve students understanding and creativity. Optimizing the PjBL learning model is one of the solution as an effort to overcome this problem. The results of the study show that the PjBL learning model is effective in improving students understanding and creativity in the Engineering Physics course at the Electrical Engineering Education Study Program at the State University of Jakarta.